Factores sociodemográficos y nivel de percepción del familiar sobre calidad del cuidado de enfermería en la unidad de cuidados intensivos del Hospital Víctor Lazarte Echegaray - Robles Benzaquen, Mónica Maribel (2016)
This study research, type quantitative, descriptive – correlational, cross- sectional, conducted in order to establish the correlation between socio demographic factor and level of perception of family of the patient hospitalized intensive care unit Hosptial Víctor Lazarte Echegaray. The sample consited of 26 family , wich was obtained by simple random sampling with a significance level of 5% and a sampling error of +- 7%. ). Two instruments were used : structured questionnaire of demographic factors: age, sex, degree of instruction and origin; and scale of measurement of perception of care nursing (Cronbach Alpha reliability = 0.756). The information obtained was tabulated and processed using statistical test of chi square (X2). The results show that the socio demographic factors are factors that singnificantly influence the level of perception of the family on the nursing care in the patient hospitalized in the intensive care unit.